Effect of PAH Specific Therapy on Pulmonary Hemodynamics and Six-Minute Walk Distance in Portopulmonary Hypertension: A Systematic Review and Meta-Analysis. (13th November 2014) - Faisal, Muhammad; Siddiqi, Furqan; Alkaddour, Ahmad; Bajwa, Abubakr A.; Shujaat, Adil
Abstract : Background . Little is known about the effect of pulmonary arterial hypertension (PAH) specific therapy on pulmonary hemodynamics and exercise capacity in patients with portopulmonary hypertension (PoPH) because such patients are usually excluded from randomized clinical trials (RCT) of such therapy. Methods . We searched PUBMED using the terms "(Therapy/Broad (filter)) AND (portopulmonary hypertension)." We included studies that met the following criteria: ≥5 patients, AND PoPH confirmed by right heart catheterization (RHC), AND follow-up RHC data, AND/OR baseline and follow-up 6MWD available. Results . 12 studies met our inclusion criteria. None was a RCT. The baseline mPAP was 48.6 ± 4.4 mmHg, cardiac output (CO) 5.6 ± 0.9 L/min, and pulmonary vascular resistance (PVR) 668.6 ± 219.1 dynes.sec/cm 5 . The baseline 6MWD was 348.2 ± 35.6 meters. The use of PAH specific therapy improved mPAP by 7.54 mmHg (95% CI 10.2 to 4.9), CO by 1.77 L/min (95% CI 1.1 to 2.4), and PVR by 253 dynes.sec/cm 5 (95% CI 291.4 to 214.6) (n = 135 ) and 6MWD by 61.8 meters (95% CI 47.5 to 76) (n = 122 ). Conclusions . The use of PAH specific therapy in PoPH results in significant improvement in both pulmonary hemodynamics and 6MWD.